A CIPP Model Evaluation: Advancing Learning Through Interest Based-Learning Media Program in Higher Education - Almubarak, Almubarak; Nahadi, Nahadi; Sriyati, Siti; Adhani, Aidil; Yasim, Sukmawati (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2026)
Evaluation of interest-based education programs is an essential component of assessing a program's effectiveness in higher education. However, valid, contextual, and relevant instruments for curriculum development objectives, such as those in chemistry education, remain limited. The purpose of this study was to determine how to (1) design and develop program evaluation instruments based on the Context, Input, Process, Product (CIPP) model, (2) program effectiveness by looking at evaluation results in each aspect of the model, and (3) relevance between evaluation results and the Model structure. The study used an evaluative approach with the CIPP evaluation model as the main framework. The instrument was developed independently and validated by experts with a logical-theoretical-empirical approach, with samples of chemistry education students in the chemistry learning media lecture program. Data were collected using a questionnaire, analysed using a statistical approach, and the evaluation results were reported. The evaluation results show that (1) the designed and developed evaluation instrument meets the valid criteria (0.91 or high validity), (2) this program has high effectiveness with an average score of Context (3.75), Input (3.5), Process (3.0), and Product (3.5), and (3) the evaluation results show relevance to the model structure and can be used effectively. These results confirm that the CIPP model can not only measure program effectiveness, but also identify areas that still need improvement for continuous improvement. CIPP model-based evaluation can be an effective tool for assessing the effectiveness of interest-based lecture programs in higher education.